Changes in Jail Admissions Before and After Traumatic Brain Injury - Schwartz, Joseph A. (Journal of quantitative criminology, 2022)
Objectives Traumatic brain injury (TBI) is differentially concentrated within incarcerated populations. Despite the consistency of this observation, the timing of within-individual changes in criminal justice contact in relation to TBI remains under-investigated. For example, previous studies have primarily considered TBI as a causal influence of later criminal justice contact. However, TBI may also serve as a consequence of criminal justice contact or a criminogenic lifestyle. The current study simultaneously observes both possibilities by examining criminal justice contact before, around the time of, and after the first reported TBI. Methods Drawing from a combination of self-report and lifetime official record data from a jail cohort admitted between February 2017 and September 2017 and who sustained their first reported TBI at age 21 or older ( N = 531), the current study examines jail admissions in the 24 months before and 24 months after the first reported TBI and across eight biannual intervals ( N = 4,248 person-periods). Results Any and misdemeanor admissions slightly increased pre-TBI and continued to increase around the time of and following TBI, never returning to pre-TBI levels. Felony admissions remained stable around the time of injury and increased post-TBI. Further analyses that incorporated a comparison group revealed that these patterns are unique to the TBI group and not a result of a larger systematic process. Conclusions These findings indicate that the probability of jail admission is greatest post-TBI, but also increases leading up to sustaining a TBI.